Nonproductive Models of Surnames Formation in Anthroponymicon of Lutsk Area (Linguostylistic Studies, 2017)
The article deals with the problem of lexico-semantic peculiarities of the Ukrainian local surname system revealed in Lutsk. The article analyzes the surnames with the suffixes -ець and -лo, which are characterized by quite low productivity. The anthroponyms, which can be qualified as units of double motivation of word-formation predominate among the surnames on -ець. The author considers surnames, derived from the old Slavic or Christian names mainly as names of double word-building motivation. It has been revealed that the surnames motivated by appellatives with an initial meaning of diminutiveness or subjective evaluation and those indicating to profession have been created in lexico-semantic way. The surnames on -лo mostly have the meaning of the agent’s or person’s characteristics in regard to some kind of funny character feature or some defects in pronunciation. Predominantly they have been formed from nicknames and are motivated mainly by appellatives from the category nomina personalia and nomina inpersonalia. Most of the analyzed surnames represent interesting, but lost or neglected lexical units.
Keywords: surname; anthroponym; oykonym; appellative; personal name; suffix; semantic group